2020
DOI: 10.3389/fimmu.2020.01306
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells, a New Player in Reducing Complications From Liver Transplantation?

Abstract: In response to the global burden of liver disease there has been a commensurate increase in the demand for liver transplantation. However, due to a paucity of donor organs many centers have moved toward the routine use of marginal allografts, which can be associated with a greater risk of complications and poorer clinical outcomes. Mesenchymal stromal cells (MSC) are a multi-potent progenitor cell population that have been utilized to modulate aberrant immune responses in acute and chronic inflammatory conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 141 publications
(114 reference statements)
0
7
0
Order By: Relevance
“…How to establish immune tolerance to avoid the complications caused by long-term use of immunosuppressants has become the ultimate goal in the field of transplantation. In many explorations, MSC-based therapy has attracted increasing attention in solid organ transplantation, [21][22][23][24] especially genetic modification, which has enhanced the therapeutic effects of MSCs and greatly expanded their therapeutic prospects. [25][26][27] However, accumulating evidence suggests that MSCs exert their therapeutic effects, which is mainly attributed to their ability to interact with injured tissues by releasing soluble bioactive factors (ie paracrine function), rather than long-term integration into host tissues.…”
Section: Discussionmentioning
confidence: 99%
“…How to establish immune tolerance to avoid the complications caused by long-term use of immunosuppressants has become the ultimate goal in the field of transplantation. In many explorations, MSC-based therapy has attracted increasing attention in solid organ transplantation, [21][22][23][24] especially genetic modification, which has enhanced the therapeutic effects of MSCs and greatly expanded their therapeutic prospects. [25][26][27] However, accumulating evidence suggests that MSCs exert their therapeutic effects, which is mainly attributed to their ability to interact with injured tissues by releasing soluble bioactive factors (ie paracrine function), rather than long-term integration into host tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Shortly after that, this technique was suggested for the treatment of liver cirrhosis and fibrosis. MSCs in the range of 10 5 -10 9 are infused by intravenous, intrahepatic, or intrasplenic injection; however, it is unclear whether this therapy contributes to liver regeneration in the long period [32,33]. In 2017, MSC Tx was reported to treat liver graft rejection; it was found that liver functions and allograft histology were improved in addition to Treg/Th17 ratio, CD4 + Tcell activation [34].…”
Section: Nonparenchymal Cell Transplantationmentioning
confidence: 99%
“…Besides, the liver comprises parenchymal cells, such as hepatocytes, cholangiocytes, and LSPCs, as well as nonparenchymal cells, such as HSCs, LSECs, KCs, and other immune cells, both of which can present antigens as well as secrete cytokine and chemokine, thereby initiating immune responses [35][36][37].…”
Section: The Structure Of the Livermentioning
confidence: 99%